2020
DOI: 10.1155/2020/8010376
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions among the Heavy Metals in Soils and in Weeds and Their Antioxidant Capacity under the Mining Activities in Thai Nguyen Province, Vietnam

Abstract: In this study, the relationship between heavy metals (HMs) concentrations in soils and several weeds including Cyclosorus parasiticus, Dicranopteris linearis, Pityrogramma calomelanos, and Pteris vittata in three mining sites (Cam Gia (Thai Nguyen city), Tan Long (Dong Hy district), and Ha Thuong (Dai Tu district)) in Thai Nguyen province, Vietnam, have been investigated. The levels of HMs varied among soil origins and showed the contaminations of As, Cu, and Pb in soil samples collected in Dong Hy and Dai Tu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Moreover, P. vittata can grow and develop normally on Zn-contaminated soil because it can accumulate Zn in leaves up to 737 mg/kg. In Vietnam, P. vittata and some other ferns have been used to remedy metal-contaminated soil in the Thai Nguyen mine with plants [ 22 , 71 , 72 ]. In 1999, Singh et al reported that a decoction of Pteris vittata was effective in the treatment of dysentery [ 63 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, P. vittata can grow and develop normally on Zn-contaminated soil because it can accumulate Zn in leaves up to 737 mg/kg. In Vietnam, P. vittata and some other ferns have been used to remedy metal-contaminated soil in the Thai Nguyen mine with plants [ 22 , 71 , 72 ]. In 1999, Singh et al reported that a decoction of Pteris vittata was effective in the treatment of dysentery [ 63 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%
“…In addition, some other studies have also described the composition of P. vittata , with glycosides of apigenin, luteolin, quercetin, kaempferol, leucocyanidin, and leucodelphinidin [ 65 ]. In the pharmacological field, several studies have shown that P. vittata has antioxidant, hypoglycemic, anti-inflammatory, antiplatelet, and anticancer activities [ 72 , 73 , 74 ]. Recently, Nguyen and coworkers revealed the mechanism of metal accumulation in P. vittata dominating the Thai Nguyen mining sites.…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%
“…In order to evaluate antioxidant properties of P. vittata aerial and subterranean parts, dry extracts of these above-mentioned plant samples were dissolved at 100 μg/mL by DMSO. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay followed our previously described method with ascorbic acid as positive control (Nguyen et al, 2020).…”
Section: Evaluation Of Antioxidant Activitiesmentioning
confidence: 99%